(untitled) (Bioscience Journal, 2015)
In this work, a virus isolate collected from squash plants (Cucurbita pepo L.), showing severe symptoms of mosaic and leaf deformation, grown in Cuba, was analyzed using indicator plants, electron microscopy, and phylogenetic analysis. Plants of Squash, cv. Caserta, inoculated with this virus isolate showed mosaic, leaf distortion and blistering symptoms, whereas papaya plants were immune and did not show any symptoms. A transmission electron microscopic examination of leaf dip preparations made from infected squash leaves revealed the presence of elongated and flexuous particles, approximately 780-800 x 12 nm in size. Genomic fragments containing the coat protein (CP) and HC-Pro genes, amplified by specific primers for Papaya ringspot virus, W strain (PRSV-W), showed amino acid identities of both genes higher than 94% when compared to other PRSV-W isolates from America. In the phylogenetic tree, this virus isolate has grouped with other virus isolates from America, Australia, and India and was more distant from the Asian isolates. Taken together, the analyses allow the conclusion that this virus isolate is a W strain of PRSV, detected for the first time in Cuba.